Acute Kidney Injury after Isolated Coronary Bypass Surgery - Slaughter, John C.; Davenport, Daniel L.; Saha, Sibu P. (International Journal of Angiology, 2024)
Acute kidney injury (AKI) is among the most serious of the common postoperative complications of cardiac surgeries, which can increase the short- and long-term morbidity and mortality of patients. This study aimed to examine possible risk factors that lead to AKI. We sought to compare our AKI rates to national averages in coronary artery bypass grafting (CABG) reported by the Society of Thoracic Surgeons (STS). We reviewed our institution's data for renal failure in CABG procedures performed between January 1, 2020, and June 30, 2023. From the database, we identified 1,068 CABG patients and reviewed demographics, nonmodifiable conditions, and modifiable risk factors. The STS database uses the Risk, Injury, Failure, Loss, and End-stage renal disease definition for renal failure. Of our patient sample, 14 (1.3%) experienced renal failure. The national rate for AKI after isolated CABG was 1.9% in 2023. Chronic lung disease was a risk factor for AKI development. The mean perfusion, cross-clamp, ventilator times, and hospital stay increased in AKI patients. All patients who suffered from AKI had undergone perioperative blood transfusion. Our single-center experience with renal failure is slightly better than the national average. In our population, chronic lung disease and lower preoperative ejection fractions were associated with increased rates of AKI. Modifiable risk factors in our population included perioperative blood transfusion and increased perfusion/cross-clamp times. Lastly, AKI patients spent longer time on ventilators, increased lengths of stay, and increased postoperative mortality.
Keywords: acute kidney injury; coronary artery bypass grafting; cardiac surgery; cardiac surgery associated AKI; renal failure; acute kidney insufficiency; society of thoracic surgeons database